Inception and Evolution of Nitrogen Sorption Hysteresis Loops by Thermally-Induced Nanopore Drilling in TiO Xerogel Microspheres: UV Photoreduction of Methyl Orange - Celso Velásquez; M. Luisa Ojeda; Antonio Campero; J. Javier Sánchez-Mondragón; J. Marcos Esparza; Fernando Rojas (Adsorption Science & Technology)
Titanium dioxide (TiO 2 ) microspheres were prepared via a sol–gel route and the textural properties of these substrates developed through thermal treatment performed between 100 °C and 500 °C which led to the decomposition of organic groups and sintering between microparticles. The annealed TiO 2 microglobules enclosed a nanopore network consisting of alternating bulges and throats. The nitrogen adsorption isotherms of the TiO 2 xerogels treated at 100 °C and 500 °C possessed very narrow hysteresis loops, whereas the corresponding adsorption isotherms of the TiO 2 microglobular samples annealed at 200–400 °C showed well-defined hysteresis cycles. The UV catalytic photoreduction of Methyl Orange solutions in the presence of porous TiO 2 microspheres occurred to a significant extent regardless of the annealing temperature employed; anatase was present between 200 °C and 500 °C while the appearance of rutile started from 350 °C onwards. Electron release took place from the external area of the microglobules rather than from the surface of the internal pores of the microspheres; as a consequence, significant photocatalytic activity was displayed by all the samples. Two concomitant effects influenced the properties of a given TiO 2 sample: (i) an increase in the annealing temperature led to a higher crystallinity; and (ii) the surface area and porosity decreased with temperature due to increased sintering.